E-government and e-commerce issues in Malaysia - Yousef A. Baker, El-Ebiary; Julaily Aida, Jusoh; Anas Ghassan, Kanaan; Pathmanathan, P.R.; Nahg Abdulmajid, Alawi; Amer, Hatamleh; Lowai Saleh, Aledinat; Khairi, Aseh; Samer, Bamansoor (2021)
In Malaysia , an e - commerce company is still considered a new middleman. As well as the development of information and communication technology strongly affects business companies at the present time in terms of management, business strategies, production, sales and marketing, and other aspects that underpin business profitability in general. E - commerce , known as e - commerce , refers to a general term for a commercial activity using modern technologies, or a commercial transaction that includes the exchange of data via electronic frameworks, especially the Internet, as well as many modern systems used in personal computers, smart phones, etc. It is not just limited to doing business between companies but also related to online services between governments and individuals. Various investigations related to e - commerce have identified obstacles related to information technology (IT) organization, internet use, financial situation, government and administrative activities as important determinants of doing business online. Information and Communication Technology (ICT) has revolutionized businesses around the world. In this paper, e - commerce practices in Malaysia are analyzed by their characteristics, drawbacks, openings and risks. This paper provides a general review of the current issues considered by e - commerce organizations today. It also suggests the challenges and problems facing e - commerce companies at the present time and how to solve them using e - commerce concepts.